Relationship between Strategic Alliances and Firm Performance in Emerging Markets in Sudan - Alex, Angela (Journal of Strategic Management, 2024)
Purpose: The aim of the study was to assess the relationship between strategic alliances and firm performance in emerging markets in Sudan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study on the relationship between strategic alliances and firm performance in emerging markets, specifically in Sudan, revealed several key findings. Firstly, it was observed that strategic alliances play a crucial role in enhancing firm performance in Sudan's emerging market context. These alliances provide access to resources, capabilities, and knowledge that are otherwise scarce or unavailable to firms operating in such environments. Additionally, the study found that strategic alliances enable firms to mitigate risks associated with operating in uncertain and volatile markets like Sudan by sharing costs, technology, and market insights with their partners. Furthermore, firms engaged in strategic alliances demonstrated improved competitiveness and innovation capabilities, which translated into enhanced financial performance and market positioning. Overall, the findings underscore the significance of strategic alliances as a strategic tool for firms seeking to navigate the challenges and capitalize on the opportunities present in Sudan's emerging market landscape. Implications to Theory, Practice and Policy: Institutional theory, resource-based view and network theory may be use to anchor future studies on assessing relationship between strategic alliances and firm performance in emerging markets in Sudan. Provide practical guidance for firms operating in emerging markets on how to effectively form and manage strategic alliances. Advocate for policy reforms that promote a conducive environment for strategic alliances in emerging markets.